Answers

2015-11-15T14:06:15+05:30
Hi there,
a=√7+1
then -6/a=-6/√7+1
=-6(√7-1)/6  {by rationalizing the denominator }
there fore -6/a=√7-1
i hope this helps u...
0
2015-11-15T14:16:38+05:30
given, a =1 +√7
therefore 1 / a = 1 / ( 1+√7 ) 
= 1 / ( 1+√7 ) * ( 1-√7 ) / ( 1-√7 )
= 1 - √7 /1² - √7²
= ( 1 - √7 ) / 1 - 7
= 1 - √7 / -6
therefore value of 1 / a = 1 - √7 / - 6
now,
- 6 / a ,
= - 6 / 1 - √7 / -6
= -6 * -6 / 1 - √7
= 36 / 1 - √7
= 36 (1 +√7 ) / ( 1 -√7 )( 1+√7 )
= 36 ( 1+ √7 ) / 1² - √7²
= 36 + 36√7 / 1 - 7
= 36 + 36√7 / - 6
= 36 (1 + √7 ) / - 6
= 6 ( 1 + √7 ) / -1
= - 6 - 6√7
therefore the value of -6 / a is  - 6 - 6√7 .
   i hope this answer will help u........................................^_^
1 5 1